Work, Ergonomics and Industrial Relations - Lamonde, Fernande; Montreuil, Sylvie (Relations industrielles / Industrial Relations, 1995)
Two objectives are pursued: to define the object of study, the objectives and the methodology that are characteristic of ergonomics, and to highlight the common points and possibilities of collaboration between industrial relations and ergonomics. The interest inherent in a collaboration between these 2 disciplines is explained, among other things by a historical coincidence. On the ergonomics side, a period that concentrated on developing concrete ways of collaborating with technical disciplines like engineering, computing and architecture has given way to a focus on work organization and the social management aspect of ergonomics intervention. At the same time, industrial relations has developed a more pronounced interest in the practical management problems that are posed by micro-organizational processes within firms, namely, the informal work activities of operators.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Ergonomics; Labor Unions; Labor relations; Objectives; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Le travail humain, l'ergonomie et les relations industrielles - Lamonde, Fernande; Montreuil, Sylvie (Relations industrielles / Industrial Relations, 1995)
Avec ce numéro thématique, la revue Relations industrielles/Industrial Relations publie pour la première fois des articles en ergonomie. De ce fait, le présent article vise deux objectifs: définir l'objet d'étude, l'objectif et la méthodologie d'intervention propres à l'ergonomie et mettre en lumière les points de rencontre et les perspectives de collaboration entre relations industrielles et ergonomie. L'intérêt porté à la question de la collaboration entre ces deux disciplines est expliqué, entre autres, par une «coïncidence historique ». Du cóté de l'ergonomie, la popularité des volets « organisation du travail » et « gestion sociale de l'intervention ergonomique » succéderait à une période où les énergies ont été concentrées sur le développement de modalités concrètes de travail en commun avec les disciplines techniques comme l'ingénierie, l'informatique et l'architecture. Parallèlement à cela, du cóté des relations industrielles s'est développé un intérêt de plus en plus marqué pour les problèmes pratiques de gestion posés par les micromécanismes organisationnels que représente, dans l'entreprise, l'activité réelle et informelle des opérateurs. Trois formes concrètes de collaboration à faire naître entre ergonomes et spécialistes en relations industrielles sont proposées.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Ergonomics; Labor Unions; Labor relations; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z